2018
DOI: 10.1111/bju.14249
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of prostate artery embolization for benign prostatic hyperplasia: an observational study and propensity‐matched comparison with transurethral resection of the prostate (the UK‐ROPE study)

Abstract: Our results indicate that PAE provides a clinically and statistically significant improvement in symptoms and QoL, although some of these improvements were greater in the TURP arm. The safety profile and quicker return to normal activities may be seen as highly beneficial by patients considering PAE as an alternative treatment to TURP, with the concomitant advantages of reduced length of hospital stay and need for admission after PAE. PAE is an advanced embolization technique demanding a high level of expertis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
188
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(207 citation statements)
references
References 17 publications
11
188
0
8
Order By: Relevance
“…We noted a mean prostate volume reduction that was slightly superior when compared with the other studies in literature. 7,8,12,17,18 These data might be referred to the high skill of our interventional radiologists that led to bilateral prostatic arteries embolisation in 80% of treated patients.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…We noted a mean prostate volume reduction that was slightly superior when compared with the other studies in literature. 7,8,12,17,18 These data might be referred to the high skill of our interventional radiologists that led to bilateral prostatic arteries embolisation in 80% of treated patients.…”
Section: Discussionmentioning
confidence: 83%
“…Patients treated with PAE using the PErFecTED technique reported higher outcomes improvement compared with patients treated with the standard technique . Performed as 1 day surgery procedure, PAE reports only a few complications, while preserving ejaculation and sexual function, and significant symptoms and quality of life improvement in patients with BPH . In this study, we report the results of PAE, focusing on sexual and functional outcomes, as a primary treatment in 147 patients with severe LUTS not eligible for surgery or wishing to postpone more invasive treatments and their sexual‐related adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…The recent UK Register of Prostatic Embolisation (ROPE) study has shown its preliminary safety and efficacy in a multicentre observational evaluation, which also included an indirect comparison with TURP 3. This study follows other small randomised controlled trials suggesting some benefit of PAE over TURP,4 and in a linked article (doi:10.1136/bmj.k2338), a larger trial adds further detail to PAE’s ongoing evaluation 5…”
mentioning
confidence: 77%
“…Seventy‐one percent of PAE cases were performed as outpatients or day cases. By contrast, 80% of TURPs required at least one night of hospital stay and a majority two nights .…”
mentioning
confidence: 94%